Changes in the physiological characteristics and baicalin biosynthesis metabolism of Scutellaria baicalensis Georgi under drought stress - Cheng, Lin; Han, Mei; Yang, Li-min; Li, Yang; Sun, Zhuo; Zhang, Tao (Industrial crops and products, 2018)
•Appropriate drought can increase the content of secondary metabolites.•Drought measures for production should pay attention to timeliness.•Providing a simple method to increase the content of secondary metabolites. Drought stress is an important ecologically limiting factor that strongly affects the physiological and biochemical reactions of medicinal plants and changes the secondary metabolic process. Scutellaria baicalensis Georgi (SBG), belonging to the Lamiaceae family, is a traditional medicinal herb that is well known for its high flavonoid content. Baicalin is the most important bioactive constituent of these flavonoids. In the current study, the effects of progressive drought stress on plant physiological characteristics and the secondary metabolism of baicalin were investigated during the vegetative period in two-year-old SBG. The results showed that the relative water content of leaves was reduced, fresh and dry root weight decreased significantly, the contents of malondialdehyde (MDA), proline (Pro), soluble sugar (SS) and soluble protein (SP) increased, and the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR) increased during mild and moderate drought but were inhibited in severe drought. The content of baicalin increased significantly under mild drought stress but decreased under severe stress. Meanwhile, the expression patterns and activities of key enzymes upstream of baicalin biosynthesis including Phenylalanine ammonialyase (PAL), Cinnamate-4-Hydroxylase (C4H), 4-Coumarate:Coenzyme A Ligase (4CL) and Chalcone Synthase (CHS), which were in the secondary metabolic pathways, were consistent with the accumulation of baicalin. These results demonstrate that an appropriate degree of drought stress may promote baicalin accumulation by stimulating the expression and activities of the key enzymes involved in baicalin biosynthesis; in this process, antioxidant enzyme was closely related to the key enzyme of secondary metabolic pathway, which plays an important role in regulating the active ingredient accumulation which plays an important role in regulating baicalin accumulation. During agricultural production, SBG should not be harvested after prolonged drought but instead should be harvested several days after rain or irrigating to ensure high baicalin content.